Effects of potassium fluoride salt additive on the sintering temperature and dielectric properties of BaFe0.5Nb0.5O3 ceramics - Intatha U. (2014)
BaFe0.5Nb0.5O3 (BFN) exhibits very high dielectric constant over a wide temperature range. However, these materials normally require high-temperature sintering to achieve a maximum densification. The aim of this study is to determine the effect of potassium fluoride salt on the sintering and dielectric properties of BFN ceramics. The results show that KF additive lower the sintering temperature by 100-200°C without affecting the formation of BFN phase. Ceramics doped with 1% KF show optimum densities of about 95% of the theoretical value when sintered at 1300°C. The addition of fluoride salt in the BFN ceramics causes very broad dielectric constant curves over a wide temperature range indicating the diffuse phase transition characteristic. Furthermore, this addition also reduces in the dielectric loss when compared with pure BFN ceramics. © 2008 Trans Tech Publications, Switzerland.